The benefit of giving a single dose of antibiotics before cystoscopy in preventing urinary infection following endoscopy A study at Tishreen university hospital (2021 - 2022) - Mahmoud, Ahmad; Hassan Naser,; Louai Naddaf , (Latakia University Journal -Medical Sciences Series, 2023)
Objective: The aim of the research is studying the effectiveness of giving a single dose of prophylactic antibiotic before cystoscopy in the prevention of urinary infection Methods: Study type: A Retrospective Observational Study The research sample included 200 patients who underwent cystoscopy under local anesthesia in the Department of Urology at Tishreen University Hospital in Lattakia during the time period 2021-2022, and the investigators met the criteria for inclusion in the research . The patients' ages ranged from 18 to 77 years, with a mean age of 56 ± 7.3 years Results: Patients were divided into two groups according to the administration of prophylactic antibiotics before endoscopy (100 cases in each group). After the endoscopy procedure, local and systemic clinical symptoms developed in patients in both groups, but there were no statistically significant differences between the two groups. Urinary burning was the most frequent clinical presentation. A urine test was performed and it was positive for 7% in the antibiotics group, compared to 9% in the other group, without statistical significance . The frequency of positive urine examination was higher in the absence of antibiotics in patients over 60 years of age with a statistical significance (p: 0.001), in patients with diabetes with a statistical significance (p: 0.002), in patients with hypertension with a statistical significance (p: 0.0001),and antibiotics in patients undergoing invasive procedures such as bladder biopsy with a statistical significance (p: 0.02) Conclusions: There is no need to use a preventive antiseptic before simple cystoscopy in healthy patients of middle age.It is recommended to use the prophylaxis antibiotics before cystoscopy with patient that there are specific risk factors (advanced ages - chronic diseases - traumatic procedures) that predispose to the development of urinary infection. Key words:. pyuria - bacteriuria - prophylaxis antibiotic - urinary infection - cystoscopy